Stable and Highly Immunogenic MicroRNA-Targeted Single-Dose Live Attenuated Vaccine Candidate against Tick-Borne Encephalitis Constructed Using Genetic Backbone of Langat Virus - Konstantin A. Tsetsarkin (American Society for Microbiology, 2019)
ABSTRACT Tick-borne encephalitis virus (TBEV), a member of the genus Flavivirus, is one of the most medically important tick-borne pathogens of the Old World. Despite decades of active research, attempts to develop of a live attenuated virus (LAV) vaccine against TBEV with acceptable safety and immunogenicity characteristics have not been successful. To overcome this impasse, we generated a chimeric TBEV that was highly immunogenic in nonhuman primates (NHPs). The chimeric virus contains the prM/E genes of TBEV, which are expressed in the genetic background of an antigenically closely related, but less pathogenic member of the TBEV complex—Langat virus (LGTV), strain T-1674. The neurovirulence of this chimeric virus was subsequently controlled by robust targeting of the viral genome with multiple copies of central nervous system-enriched microRNAs (miRNAs). This miRNA-targeted T/1674-mirV2 virus was highly stable in Vero cells and was not pathogenic in various mouse models of infection or in NHPs. Importantly, in NHPs, a single dose of the T/1674-mirV2 virus induced TBEV-specific neutralizing antibody (NA) levels comparable to those seen with a three-dose regimen of an inactivated TBEV vaccine, currently available in Europe. Moreover, our vaccine candidate provided complete protection against a stringent wild-type TBEV challenge in mice and against challenge with a parental (not miRNA-targeted) chimeric TBEV/LGTV in NHPs. Thus, this highly attenuated and immunogenic T/1674-mirV2 virus is a promising LAV vaccine candidate against TBEV and warrants further preclinical evaluation of its neurovirulence in NHPs prior to entering clinical trials in humans. IMPORTANCE Tick-borne encephalitis virus (TBEV) is one of the most medically important tick-borne pathogens of the Old World. Despite decades of active research, efforts to develop of TBEV live attenuated virus (LAV) vaccines with acceptable safety and immunogenicity characteristics have not been successful. Here we report the development and evaluation of a highly attenuated and immunogenic microRNA-targeted TBEV LAV.